New ways of financing LDCs - Alfons Lemper (Intereconomics, 1972)
The forthcoming third plenary meeting of UNCTAD in Santiago will primarily consider how the less developed countries (LDCs) can be integrated more effectively into the world economic system. To solve the problem of development of the so-called “Third World” it is considered essential to open up new financial resources for the LDCs.
Keywords: 330; Development Policy